Effect of UV-C on the physiology and biochemical profile of fresh Piper nigrum berries - Collings, Emma R.; Alamar, M. Carmen; Cools, Katherine; Redfern, Sally P.; Terry, Leon A. (Elsevier, 2017)
Application of UV-C has been shown to enhance the biochemical profile of various plant materials. This could be used to increase biochemical load, reducing the amount of material required but still impart equivalent flavour. As spices, such as black pepper (Piper nigrum L.), are typically dried to low moisture content to create a stable product for transportation and storage, little work has explored the use of modern postharvest treatments to enhance flavour. In this work, fresh P. nigrum berries were exposed to four UV-C doses (0, 1, 5 and 15 kJ m−2) and subsequently stored at 5 °C for ca. 4 weeks. Two separate experiments (early and late season) were conducted across one season. Replicate P. nigrum berry clusters were stored separately within continuously ventilated 13 L boxes. Real-time respiration rate (ex situ), ethylene production, fruit colour and water potential were measured at regular intervals during storage. In addition, piperine and essential oils were assessed using a simple newly developed method which enabled both compound groups to be simultaneously extracted and subsequently quantified. UV-C was found to cause significant changes in colour (from green to brown) whilst also altering the biochemical composition (piperine and essential oils), which was influenced by UV-C dose and berry maturity. Low to medium UV-C doses could potentially enhance flavour compounds in black pepper enabling processors to create products with higher biochemical load.
Keywords: Black pepper; Real-time respiration rate; Ethylene; Piperine; Essential oils